2015
DOI: 10.1039/c5ta04934b
|View full text |Cite
|
Sign up to set email alerts
|

Substituent effect of Ru(ii)-based sensitizers bearing a terpyridine anchor and a pyridyl azolate ancillary for dye sensitized solar cells

Abstract: In this study we explore the substituent effects of a class of Ru(II)-based sensitizers bearing a 4,4 0 ,4 00tricarboxy-2,2 0 :6 0 ,2 00 -terpyridine anchor, a functional pyridinyl azolate and a single thiocyanate ligand. Three sensitizers, i.e. PRT-tBu, ND-1 and ND-2, with t-butyl, 5-[4-[bis(4-hexyloxyphenyl)amino]phenyl]-2-thienyl and 5-[7-[4-[bis(4-hexyloxyphenyl)amino]phenyl]-4-(2,1,3-benzothiadiazolyl)]-2-thienyl substituents are designed and synthesized. Their photophysical and redox properties are probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Indeed, with the development of novel synthetic methods, the repertoire of fluorinated pyrazole ligands has increased dramatically in recent years. It is impossible to consider in this review each individual example in detail, but the list of structures with fluorinated pyrazoles prepared during the past 5 years and brief descriptions of their applications with references are outlined in Figure . …”
Section: Applications Of Fluorinated Pyrazolesmentioning
confidence: 99%
“…Indeed, with the development of novel synthetic methods, the repertoire of fluorinated pyrazole ligands has increased dramatically in recent years. It is impossible to consider in this review each individual example in detail, but the list of structures with fluorinated pyrazoles prepared during the past 5 years and brief descriptions of their applications with references are outlined in Figure . …”
Section: Applications Of Fluorinated Pyrazolesmentioning
confidence: 99%
“…On the other hand, Eqs. (10) and (12) indicate that one thiocyanate ligand is sufficient for the regeneration of the thiocyanate‐containing ruthenium sensitizer efficiently . When more than one thiocyanate ligand exist in the complex, the positive charge on S will be diluted by dispersing it on more than one thiocyanate ligands, which weakens the interaction between the thiocyanate sulfur and iodide species.…”
Section: Description Of the Dye Regeneration Sites Of The Thiocyanatementioning
confidence: 99%
“…Recently, Chang et al [ 131 ] reported pyrazolyl-pyridine ancillary ligands bearing a series of donor groups in which the simplest substituents (such as t -butyl group) leads to better efficiency with respect to the triphenylamino and benzothiadiazolylgroups.…”
Section: Modifications Of Black Dye and Structure-properties Relatmentioning
confidence: 99%